Correlation analysis of serum CHI3L1, HMGB1 and CD62E detection with the prognosis of Mycoplasma pneumoniae in children: Serum CHI3L1, HMGB1 and CD62E in Mycoplasma pneumoniae in children - Yang, Hui; Zhang, Tingli; Zhang, Xiaoqi; Yang , Xu; Jiang, Xiaoan; Chen, Bo (Journal of Medical Biochemistry, 2026)
[Objective] To evaluate the clinical value of serum Chitinase-3-like protein 1 (CHI3L1), high mobility group protein 1 (HMGB1), and CD62E detection for determining the severity and prognosis of Mycoplasma pneumoniae in children. [Methods] A total of 476 children with Mycoplasma pneumoniae who were diagnosed and treated at this hospital from January 2023 to March 2025 were selected as the Mycoplasma pneumoniae infection group. The healthy control group consisted of 120 kids who had hospital examinations over the same time period. Serum CHI3L1, HMGB1, and CD62E levels were examined between the Mycoplasma pneumoniae infection group and the healthy control group. To investigate the risk factors for a bad outcome in kids infected with Mycoplasma pneumoniae, univariate and multivariate logistic regression analyses were employed. Serum CHI3L1, HMGB1, and CD62E levels were investigated in relation to Mycoplasma pneumoniae severity and their predictive power for a poor outcome. [Results] HMGB1, CD62E, and CHI3L1 serum levels were significantly greater in the Mycoplasma pneumoniae infection group than in the healthy control group (P<0.05), and they increased as Mycoplasma pneumoniae infection severity increased (P<0.05). The proportion of children with Mycoplasma pneumoniae with pleural effusion, the proportion of children with a treatment course of ≥7 days, the white blood cell count, the duration of antibacterial drug use, and the levels of serum CHI3L1, HMGB1 and CD62E in the poor prognosis group were significantly greater than those in the good prognosis group (P<0.05). However, no statistically significant differences were seen in CRP levels, age, or sex (P>0.05). Elevated serum CHI3L1, HMGB1, and CD62E levels were found to be independent risk factors for the prognosis of Mycoplasma pneumoniae by multivariate analysis (P<0.05). The levels of serum CHI3L1, HMGB1 and CD62E have relatively high efficacy in predicting the poor prognosis of Mycoplasma pneumoniae patients. The sensitivity of the combined detection of the three was 97.9%, the specificity was 90.2%, and the area under the curve was 0.785, which was significantly greater than that of the individual detection of CHI3L1, HMGB1 and CD62E (Z=3.257, 3.429, 4.650, P<0.05). [Conclusion] The levels of serum CHI3L1, HMGB1 and CD62E are indicators reflecting the severity of Mycoplasma pneumoniae. The combined detection method has high efficacy in predicting the poor prognosis of Mycoplasma pneumoniae patients.